Analytical model for composite joints under sagging moment. (15th October 2015) - Bennacer, M.A.; Beroual, A.; Kriker, A.; Demonceau, Jean-François
Highlights: Investigation of the behaviour of composite joints under sagging moment. Characterisation of a specific joint component: the concrete slab under compression. Validation of a FEM numerical tool to study the behaviour of this component. Realisation of a parametrical numerical study on this joint component. Proposal and validation of an analytical model to characterise this component. Abstract: Nowadays, modern codes and standards such as the (Eurocode 4, 2004) deal with the characterisation of steel–concrete composite joints in building structures, mainly under hogging bending moments in the beam. However, in sway composite frames or when the composite structure is subjected to an accidental/exceptional event such as earthquake or column loss, the beam-to-column joint may be subjected to sagging bending moment, a loading situation which is not yet covered by the codes. This paper deals with the behaviour of composite beam-to-column external joints under sagging bending moments, mainly focusing on the specific joint component "concrete slab in compression". Indeed, if reference is made to Eurocodes, the method recommended to characterise structural joints is the component method and the "concrete slab in compression" component has been identified as the missing component to be able to apply this method to composite joints subjected to sagging bending moment. In this article, the finite element method is used to model the slab using VecTor 2 software. Through the performed numerical simulations, the behaviour of the slab is studied in detail and an analytical model is proposed. With the proposed model, it is possible to characterise the concrete slab in compression component and so, to apply the component method to predict the mechanical properties of composite joints subjected to sagging bending moment.